Efficacy of neuroendoscopic-assisted surgery in the management of symptomatic sacral perineural (Tarlov) cysts: a technical report - Jiang, Ying; Dong, Lan; Pan, Yi-Qi; Zhao, Jun; Li, Wen-Fang; Zhang, Teng-Fei; Zhang, Ting; Dai, Da-Wei (Frontiers in Surgery, 2024)
Introduction The Tarlov cysts are pathological enlargements of the cerebrospinal fluid spaces between the endoneurium and perineurium, which can cause intolerable sciatic pain, motor impairment of lower limbs, and bladder/bowel dysfunction. Currently, the treatment results are unsatisfactory due to the low cure rates and extensive surgical trauma. Thus, there is an ongoing exploration of surgical techniques for Tarlov treatment. In the current study, we present a novel neuroendoscopic-assisted technique that combines the fenestration, leakage sealing, and tamponade of the Tarlov cyst. Methods Between January 2020 and December 2021, a total of 32 Tarlov patients were enrolled and received neuroendoscopic-assisted surgery. Their pre- and post-surgical Visual Analogue Scale (VAS) scores, major complaints, and MR imaging were recorded for comparison. Results 27 of 32 patients (84.4%) patients demonstrated immediate pain relief as their VAS scores decreased from 5.6 ± 1.5 to 2.5 ± 1.1 (p < 0.01) on the first day after surgery. At the 3-month follow-up, the patients' average VAS score continued to decrease (1.94 ± 0.8). Meanwhile, saddle paresthesia, urinary incontinence, and constipation were relieved in 6 (50%), 4 (80%), and 5 (41.7%), respectively, according to patients self-report. No surgical-related complication was observed in any of the cases. Discussion We conclude that neuroendoscopic-assisted surgery is an effective surgical method for symptomatic Tarlov cysts with minimized complications.